Children aged 3–4 years were more likely to be given mobile devices for calming purposes if they had weaker overall executive functioning. (9th March 2022) - Danet, Marie; Miller, Alison L.; Weeks, Heidi M.; Kaciroti, Niko; Radesky, Jenny S.
Abstract: Aim: Young children with weaker self‐regulation use more digital media, but studies have been limited by parent‐reported screen time measures. We examine associations between early childhood executive functioning and objective mobile device usage. Methods: The parents of 368 American children (51.6% male) aged 3–4 years of age completed standardised measures of executive functioning, parenting stress and household chaos. They provided mobile sampling data for 1 week in 2018–2019 and reported how often the children used mobile devices to calm themselves. Results: The children's mean age was about 3.8 years. A third of the children who were given devices to calm them down had weaker executive functioning in the overall and multivariable models, including working memory, planning and organisation. So did 39.7% of the children who used educational apps. Streaming videos, using age‐inappropriate apps and using the mobile device for more than1 h per day were not associated with executive functioning levels. Parenting stress and household chaos did not moderate the associations. Conclusion: This study confirms previous studies that suggesting that children with weaker overall executive functioning used devices more for calming purposes. It also raises questions about whether children with weaker executive functioning should use educational apps.